2019
DOI: 10.1101/538488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theoretical modeling on CRISPR-coded cell lineages: efficient encoding and optimal reconstruction

Abstract: Delineating cell lineages is a prerequisite for understanding the genesis of cell types. Recent studies have demonstrated the feasibility of generating and reconstructing CRISPR/Cas9-coded cell lineages. However, these works have not investigated the limitations or optimality of the encoding or reconstruction processes.Here, we surveyed a multitude of reconstruction algorithms and found hierarchical clustering, with a metric based on the number of shared Cas9 edits, provides the best reconstruction. As to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…To overcome this, instead of using linkage method, we assign the shared edits of the nodes being merged as the code of the newly created node (Fig.2C) and directly calculate SharedEdit distance between the new node and other nodes. When benchmarked against the set of input trees used in the previous study [4], we found ancestral code assignment resulted in better error rates compared to complete linkage method ( Fig.2D).…”
Section: Russell-rao (Sharededits) Metrics Is a Depth Metricmentioning
confidence: 77%
See 4 more Smart Citations
“…To overcome this, instead of using linkage method, we assign the shared edits of the nodes being merged as the code of the newly created node (Fig.2C) and directly calculate SharedEdit distance between the new node and other nodes. When benchmarked against the set of input trees used in the previous study [4], we found ancestral code assignment resulted in better error rates compared to complete linkage method ( Fig.2D).…”
Section: Russell-rao (Sharededits) Metrics Is a Depth Metricmentioning
confidence: 77%
“…When calculating metric between merged nodes (n 1 ) and other node (n 2 ), assigning shared edits of n 3 and n 4 to n 1 (denoted as n 1 ) can reduce the overestimation compared to complete linkage (which takes minimum SharedEdits of members). (D) Performances of code assignment and complete linkage are compared using the benchmark datasets used in [4]. Code assignment performs signicantly better (paired t-test).…”
Section: Russell-rao (Sharededits) Metrics Is a Depth Metricmentioning
confidence: 99%
See 3 more Smart Citations